Analisis Total Plate Count Mikroba Pada Ikan Teri Asin Di Pasar Remu Kota Sorong Papua Barat - Sukmawati Sukmawati (Mahesa Research Center, 2022)
Salting anchovy is a method of preservation with the principle of penetration of salt into fish meat, and it is influenced by various physical and chemical factors. The drying process in principle is the process of reducing the water content in the fish. The purpose of drying is to prevent bacteria and enzymes from in the fish's body. The quality and the safety of salted fish need attention, because in general the process of production and distribution of salted fish products is still simple and conventional. The purpose of this study was to determine the total number of microbial plate counts in salted anchovies at the Remu market, Sorong city, West Papua. The research method used is descriptive method, which describes the total number of microbial plate counts in a test sample. Based on the results of the research that has been carried out, it shows that from nine samples of salted anchovies at the Remu market, Sorong city, West Papua, which was tested it was stated that the product was suitable for consumption when viewed from the results of the total microbial plate count test.